2020
DOI: 10.1111/psyp.13530
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical dynamics differentiate athletes exhibiting low‐ and high‐ ACL injury risk biomechanics

Abstract: Anterior cruciate ligament (ACL) injuries are physically and emotionally debilitating for athletes,while motor and biomechanical deficits that contribute to ACL injury have been identified, limited knowledge about the relationship between the central nervous system (CNS) and biomechanical patterns of motion has impeded approaches to optimize ACL injury risk reduction strategies. In the current study it was hypothesized that high‐risk athletes would exhibit altered temporal dynamics in their resting state elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 153 publications
(220 reference statements)
0
15
0
Order By: Relevance
“…Muscle receptors, such as muscle spindles and Golgi apparatus, could significantly affect the proprioception. With ACL injury, the lack of afferent information from ACL mechanoreceptors leads to a weaker balance [21].…”
Section: Resultsmentioning
confidence: 99%
“…Muscle receptors, such as muscle spindles and Golgi apparatus, could significantly affect the proprioception. With ACL injury, the lack of afferent information from ACL mechanoreceptors leads to a weaker balance [21].…”
Section: Resultsmentioning
confidence: 99%
“…Emergent evidence has shown that athletes with poor neuromuscular control that have not experienced an injury or may have yet to experience an injury as signified by high external peak knee abduction moments during a drop vertical jump, eliciting resting-state electrocortical activity that may signify the CNS cannot effectively transition from rest to move states [19]. Technological improvements have advanced this line of research from resting to active states by developing MRI-compatible motion capture systems that can now be used to capture lower extremity biomechanics concurrent with CNS function derived from fMRI [4,15].…”
Section: Cns Alterations That Are Associated With High Acl Injury-rismentioning
confidence: 99%
“…The sensory-motor coordination error nature of injury having a potential neural basis is supported by alterations in brain functional connectivity between regions important for sensorimotor control [ 10 , 16 ] and quadriceps neural inhibition [ 17 ] being prospectively identified for athletes who subsequently experienced an ACL injury. Further, athletes who presented with high ACL injury risk landing biomechanics exhibited more deterministic, and potentially maladaptive, patterns of electrocortical activity within frequency bands important for attention, cognition, and sensorimotor control [ 18 ]. However, the CNS assessments from these studies were completed while the participant was at rest (resting-state fMRI and EEG, respectively), warranting approaches that can assess brain activity during active, lower extremity movements.…”
Section: Introductionmentioning
confidence: 99%